Mechanically Controlled, Seeded Formation of a Nanoscale Metastable Phase in Ionic Compounds - Palko, James W; Durandurdu, Murat; Kieffer, John (Nano letters, 2004)
Like in epitaxial and hetero-epitaxial growth, the structural order at internal grain boundaries may be used to control the nature of new phases that nucleate at such an interface. We demonstrate this concept via computer simulation. We predict the templated nucleation of a new metastable phase at the (310) symmetric tilt grain boundary in both NaCl and LiCl when subject to an external mechanical constraint. The level of applied stress allows one to control the extent to which this metastable phase grows with nanoscale precision. This interfacial seeding of structural transitions has potential to produce functionally patterned materials for novel logic and sensing devices.